Oral versus extra‐oral plasmablastic lymphoma: A comparative analysis of 101 cases. (31st December 2021) - Meer, Shabnum; Perner, Yvonne; Willem, Pascale
Abstract: Aims: Originally described exclusively orally in HIV‐infected patients, plasmablastic lymphoma (PBL) is increasingly described extra orally and in non‐HIV‐infected persons. The study comparatively analysed the clinico‐pathologic features of oral PBLs ( n = 55) to previously published extra‐oral PBLs ( n = 45 + 1) diagnosed over a seven‐year period at the same institution in an HIV prevalent setting in South Africa in order to clarify any distinction between oral and extra‐oral PBLs. Methods and results: Tumours were assessed histologically and immunohistochemically with CD45 (LCA), CD3, CD20, CD79a, PAX5, CD138, MUM1, BLIMP1, VS38c, Ki‐67, BCL6 and CD10 using standard protocols. Age ranged from 22 to 76 years (oral) and 9 and 59 years (extra‐oral). Most PBL patients were HIV positive [oral (84%); extra‐oral (65%)]. Male:female ratio was 2.7:1 for oral and 1.4:1 for extra‐oral PBLs. Favoured oral and extra‐oral sites were the maxilla and anus. PBLs displayed an indistinguishable immunohistochemical profile with unusually high CD45 expression (oral: 98%, extra‐oral: 84%). EBV assessed by chromogenic in situ hybridisation (ISH) showed positivity in all oral PBLs and 95% extra‐oral PBLs. MYC rearrangements (fluorescence ISH MYC break‐apart probe) were similar in all the PBLs. Conclusions: Extra‐oral PBL is identical to its oral counterpart in gender and age distribution, HIV status, morphological appearances, immunophenotypic profile and EBV association. PBL should be regarded as the same tumour irrespective of oral or extra‐oral site of origin.